Graphene : properties, preparation, characterisation and applications - Skakalova, Viera; Kaiser, Alan B. (Woodhead Publishing series in electronic and optical materials, 2021)
Graphene: Properties, Preparation, Characterization and Devices, Second Edition, provides a comprehensive look at the methods used to prepare and analyze graphene. Since the first edition's publication, there have been many advances in the understanding of graphene, in particular, its key properties and most relevant applications. Updates to this new edition include chapters on liquid exfoliation production of graphene and scanning transmission electron microscopy of graphene. New sections cover graphene's thermal, optical, mechanical, chemical and biocompatibility, with special attention paid to transport properties, a main barrier to the realization of commercial applications.